2017
DOI: 10.1155/2017/1403940
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Functional Connectivity in Small-Cell Lung Cancer Patients after Chemotherapy Treatment: A Resting-State fMRI Study

Abstract: Previous studies in small-cell lung cancer (SCLC) patients have mainly focused on exploring neurocognitive deficits associated with prophylactic cranial irradiation (PCI). Little is known about functional brain alterations that might occur due to chemotherapy treatment in this population before PCI is administered. For this reason, we used resting-state functional Magnetic Resonance Imaging (fMRI) to examine potential functional connectivity disruptions in brain networks, including the Default Mode Network (DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…Simó et al first reported the DMN functional connectivity decrease in patients with lung cancer [10]. Bromis et al demonstrated the possible negative effect of CTx in the DMN region of the brain in small-cell lung cancer populations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Simó et al first reported the DMN functional connectivity decrease in patients with lung cancer [10]. Bromis et al demonstrated the possible negative effect of CTx in the DMN region of the brain in small-cell lung cancer populations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on CRCI in lung cancer have mainly concentrated on brain structure changes and default mode network disruption (Bromis et al 2017;Simo et al 2015Simo et al , 2016Simo et al , 2018Welzel et al 2008). Bromis et al (2017) found significant FC disruptions within all the rest-state networks of lung cancer patients after chemotherapy compared with the healthy controls.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies on CRCI in lung cancer have mainly concentrated on brain structure changes and default mode network disruption (Bromis et al 2017;Simo et al 2015Simo et al , 2016Simo et al , 2018Welzel et al 2008). Bromis et al (2017) found significant FC disruptions within all the rest-state networks of lung cancer patients after chemotherapy compared with the healthy controls. Additionally, other results suggest that the reduced rest-state FC pattern within the default mode network (DMN) and the cognitive disorder were associated with cancer and chemotherapy in lung cancer patients (Simo et al 2018;Zhang et al 2019).…”
Section: Introductionmentioning
confidence: 90%
“…Although the global and regional brain network properties in breast cancer and lung cancer patients are reported in neuroimaging research using fMRI [34,35] and DTI [19], rectal carcinoma is still little.…”
Section: Network Propertiesmentioning
confidence: 99%